Integrasi Kurikulum Pertanian Di Sekolah Menengah Untuk Regenerasi Petani - Kurniasih (Jurnal Ilmu Pertanian dan Perikanan, 2025)
The farmer regeneration crisis in Indonesia poses a significant challenge to the sustainability of the national agricultural sector. The increasing average age of farmers and the declining interest of young generations in farming highlight the need for strategic interventions through the education sector. This study aims to explore the integration of agricultural curriculum in secondary schools as a means to build students’ interest and involvement in agriculture. A descriptive qualitative approach was employed, utilizing in-depth interviews, observations, and document analysis at several secondary schools in agrarian regions. The results indicate that integrated, contextual, and practice-based agricultural education programs can enhance students' understanding and motivation toward the agricultural sector. However, implementation remains hindered by limited resources, lack of teacher training, and weak policy support. Cross-sector collaboration and the utilization of flexible curriculum spaces, such as local content subjects and Pancasila student projects, emerge as promising strategies. Integrating agricultural curricula in secondary education is considered a critical step in promoting youth farmer regeneration and strengthening sustainable national food security.